I need you to read this : a novel - Maxwell, Jessa (Atria Books, 2024)
"Years ago Alex Marks escaped to New York City for a fresh start. Now, aside from trips to her regular diner for coffee, she keeps to herself, gets her perfectly normal copywriting job done, and doesn't date. Her carefully cultivated world is upended when her childhood hero, Francis Keen, is brutally murdered. Francis was the woman behind the famous advice column, Dear Constance, and her words helped Alex through some of her darkest times. When Alex sees an advertisement searching for her replacement, she impulsively applies, never expecting to actually get the job. Against all odds, Alex is given the position and quickly proves herself skilled at solving other people's problems. But soon, she begins to receive strange, potentially threatening letters at the office. Francis's murderer was never identified, turning everyone around her into a threat. Including her boss, editor-in-chief Howard Dimitri, who has a habit of staying late at the office and drinking too much. As Alex is drawn into the details surrounding her predecessor's murder, her own dark secrets begin to rise to the surface and Alex suddenly finds herself trapped in a dangerous and potentially deadly game of cat and mouse that takes her all the way from the power centers of Manhattan to Francis Keen's summer house, where her body was found and where the killer may just be waiting for her"--